How Do Peer Support and Self-Esteem Predict Normal Adjustment?: A Survey Study Among Adolescents with Visual Disabilities - Indrayani, Ni Putu Ananda Putri; Immanuel, Aria (Indonesian Journal of Disability Studies, 2024)
The purpose of this study was to determine the role of peer support and self-esteem in the normal adjustment of adolescents with visual disabilities in Bali. 24 adolescents with total blindness and 42 adolescents with low vision, aged 10 to 22 years old, were recruited using a purposive sampling method in this study. The highly reliable peer support scale, self-esteem scale, and normal adjustment scale were used to measure these variables. The results of multiple linear regression analyses showed that peer support and self-esteem significantly predicted the normal adjustment among adolescents with visual disabilities (total blindness and low vision). Furthermore, another separated multiple linear regression analysis confirmed that only self-esteem predicted normal adjustment among adolescents with total blindness condition. The implication of the results addressed the need to promote peer support and self-esteem among adolescents with visual disabilities to support their adjustment process in a not-always-inclusive environment.